Unilateral declarations and the European Court of Human Rights: Between efficiency and the interests of the applicant. Issue 5 (October 2018) - Glas, Lize R
Faced with numerous repetitive applications, the European Court of Human Rights (ECtHR) has welcomed the unilateral declaration mechanism as a way to handle these efficiently. In a unilateral declaration, the state admits a human rights violation and promises to provide redress to the applicant. On that basis, the Court strikes out an application and does not deal with its merits. Some authors and non-governmental organizations warn against losing sight of the applicants' interests whilst relying on unilateral declarations. Against this background, this article aims to establish whether unilateral declarations are indeed (mostly) used to dispose of repetitive applications and how this procedure works in practice. The second aim is to determine whether the interests of the applicants are sufficiently protected when the Court rules on unilateral declarations. The analysis is based on all 1285 unilateral declarations, which the states parties to the ECHR have proposed in the five years following 2 April 2012.